Orris and Timble : Lost and Found - Book 2 - DiCamillo, Kate; Mok, Carmen (Somerville, Massachusetts : Candlewick Press, 2025)
"Orris the rat and Timble the owl are unlikely friends. Each night, Timble visits Orris in the barn and listens to his stories. But Timble is growing up, and one evening when the owl doesnt appear as usual Orris wonders if Timble has forgotten him. Is their friendship over? Or could it be that Timble has a tale of his own to share?"-- Provided by publisher.
Keywords: Rats -- Juvenile fiction; Owls -- Juvenile fiction; Friendship -- Juvenile fiction; Rats -- Fiction; Owls -- Fiction; Friendship -- Fiction; Animal fiction; Readers (Publications)